2018
DOI: 10.1155/2018/1023490
|View full text |Cite
|
Sign up to set email alerts
|

Sensitive Detection of the Natural Killer Cell-Mediated Cytotoxicity of Anti-CD20 Antibodies and Its Impairment by B-Cell Receptor Pathway Inhibitors

Abstract: The antibody-dependent cell-mediated cytotoxicity (ADCC) of the anti-CD20 monoclonal antibodies (mAbs) rituximab and obinutuzumab against the cell line Raji and isolated CLL cells and its potential impairment by kinase inhibitors (KI) was determined via lactate dehydrogenase release or calcein retention, respectively, using genetically modified NK92 cells expressing CD16-176V as effector cells. Compared to peripheral blood mononuclear cells, recombinant effector cell lines showed substantial alloreactivity-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 26 publications
0
24
0
Order By: Relevance
“…Ibrutinib, through inhibition of ITK and other non-BTK kinases, abrogates NK-cell ADCC and ADCP in vitro (20)(21)(22) and may reduce the effectiveness of the CD20 antibody in patients. Acalabrutinib is highly selective for BTK and is not a potent inhibitor of most other kinases ( 15,23 ), suggesting that this BTK inhibitor might be more appropriate for combination therapy with antibodies. Similarly, several groups have demonstrated that the engineered CD20 antibody obinutuzumab mediates improved ADCC over rituximab ( 24,25 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ibrutinib, through inhibition of ITK and other non-BTK kinases, abrogates NK-cell ADCC and ADCP in vitro (20)(21)(22) and may reduce the effectiveness of the CD20 antibody in patients. Acalabrutinib is highly selective for BTK and is not a potent inhibitor of most other kinases ( 15,23 ), suggesting that this BTK inhibitor might be more appropriate for combination therapy with antibodies. Similarly, several groups have demonstrated that the engineered CD20 antibody obinutuzumab mediates improved ADCC over rituximab ( 24,25 ).…”
Section: Discussionmentioning
confidence: 99%
“…While monoclonal antibodies exert various mechanisms of targeting malignant cells in B-cell lymphoma, macrophage ADCP has been identified as a pre-dominant mechanism (18,28). In this light, previous reports examining ibrutinib in combination with rituximab that did not reveal synergy were mostly focused on NK-cell ADCC or relied on monocyte derived macrophages (20)(21)(22)(23)35). Exploring effector cell mechanisms is technically challenging since co-culture systems demand high levels of standardization.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-clinical studies assessing the synergistic interaction between ibrutinib and monoclonal antibodies have provided conflicting results, with a number of studies reporting that ibrutinib not only has no impact on antibody-mediated effects, rather a negative effect specifically on NK-cell mediated effects of the antibody (20)(21)(22)(23).…”
Section: Introductionmentioning
confidence: 99%
“…There are several newer techniques that rely on similar principles as the 51 Cr release assay but replace radioisotopes with natural cell products. As cells are killed they release lactate dehydrogenase and other proteases that can be quantified by supplying fluorogenic substrates in order to more accurately assess cytotoxicity without the need to perform any labeling or manipulation of target cells [38,39]. A potential drawback of relying on reporter molecules is that they may spontaneously release even from live cells.…”
Section: Measuring Adccmentioning
confidence: 99%